Pension reform and income inequality among the elderly in 15 European countries - Van Vliet, Olaf; Been, Jim; Caminada, Koen; Goudswaard, Kees P. (Munich, 2011)
"The ageing of populations and hampering economic growth increase pressure on public fi-nances in many advanced capitalist societies. Consequently, governments have adopted pen-sion reforms in order to relieve pressure on public finances. These reforms have contributed to a relative shift from public to private pension schemes. Since private social security plans are generally less redistributive than public social security, it can be hypothesized that the privatization of pension plans has led to higher levels of income inequality among the elderly. Existing empirical literature has mainly focused on cross-country comparisons at one moment in time or on time-series for a single country. This study contributes to the income inequality and pension literature by empirically analysing the distributional effects of shifts from public to private pension provision in 15 European countries for the period 1995-2007, using pooled time series cross-section regression analyses. Remarkably, we do not find empirical evidence that shifts from public to private pension provision lead to higher levels of income inequality or poverty among elderly people. The results appear to be robust for a wide range of econometric specifications."